Analysis of factors affecting strawberry farming (case: Dolat Rayat District, Karo Regency). Issue 2 (June 2021) - Pinem, N F; Pohan, A R; Gunawan, R
Abstract: This study aims to analyse the factors affecting strawberry farming in Dolat Rayat District. The analytical method used in finishing the study is the multiple linear regression model through the Cobb Douglas production function. The variables used in this study were land area, use of seedlings, use of NPK fertilizer, total labours and use of Joker pesticide. The results obtained indicate that land area, use of seedlings, use of NPK fertilizer, total labours and use of Joker pesticide together have a significant effect on strawberry production with a coefficient of determination of 0.699. Partially, land area, labours and the use of Joker pesticide did significantly influence the strawberry production. Meanwhile, the use of seedlings and the use of NPK fertilizer did not significantly affect the strawberry production.